2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.097-351
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Organization Index to Characterize Atrial Fibrillation using Wrist:Type Photoplethysmographic Signals

Abstract: The performance of photoplethysmography (PPG)-based wearable monitors to diagnose atrial fibrillation (AF) remains unknown to date. This study aims at assessing the performance of new indices quantifying the level of organization in PPG signals to diagnose AF. A database made of 18 adult patients undergoing catheter ablation of various cardiac arrhythmias was used. PPG signals were recorded using a wrist-type sensor. A 12-lead ECG was used as gold standard. ECGs were annotated by experts and selected segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The results of the present study (see additional material in [13]) constitute to the best of our knowledge a first clinical evidence of reliable AF detection using PPG sensors at the wrist. The high values of sensitivity (99%) showed in Table 1 demonstrates the potential of a wrist-located AF classifier using PPG technology.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The results of the present study (see additional material in [13]) constitute to the best of our knowledge a first clinical evidence of reliable AF detection using PPG sensors at the wrist. The high values of sensitivity (99%) showed in Table 1 demonstrates the potential of a wrist-located AF classifier using PPG technology.…”
Section: Discussionsupporting
confidence: 59%
“…The analysis of the recorded data has pointed at the fact that the addition of features based on variation of waveform morphologies (as presented in [13]) might be necessary to achieve improved algorithm performances: typical data segments depicted in Figure 1 illustrate this challenge. We observed that for a large number of AF epochs, pathological PPG waveform morphologies were recorded: see by instance Figure 1 D) and F).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power spectrum is calculated using the autoregressive (AR) model for the PRV signal, from which the features are extracted according to the frequency range to reflect the stability of cardiovascular activity within the human body and to obtain information about the variability of the cardiovascular system (Fallet et al, 2019). 1) LF_HF: the ratio of low frequency (LF) to high frequency (HF), which can reflect a balanced state of sympathetic and parasympathetic tone.…”
Section: Feature Extraction Based On Frequency Domain Analysismentioning
confidence: 99%
“…PPG sensors are fallible during movements due to the induced noise caused by motion; this leads to inaccurate readings of the PPG signal and causes false diagnosis [4]. The ANC is one of the several techniques for providing accurate PPG signals [5,6]. It depends on active filtering and utilizes the adaptive filter.…”
Section: Introductionmentioning
confidence: 99%